COMBINING ABILITY STUDIES FOR FIBRE YIELD AND ITS ATTRIBUTING TRAITS IN TOSSA JUTE ( TTRIBUTING TRAITS IN TOSSA JUTE (Corchorus olitorius Corchorus olitorius L.) - A.ANIL KUMAR1 , S. B. CHOUDHARY , H. K. SHARMA; P. G. KARMAKAR, R. T. MARUTHI, JAWAHAR LAL JATOTHU , J. MITRA (The Bioscan, 2018)
The combining ability analysis of fifteen diverse genotypes was carried out using Line x Tester mating design. Analysis of variance revealed significant differences(P<0.01) among the parents and their hybrids for fibre yield and its attributes traits.Three lines namely OIJ-268 (12.78), OMU-33 (3.22), OIJ-05 (0.28) and tester OIN-255 (4.61)revealed significant GCA effect for fibre yield and were identified as the best general combiners for the improvement of fibre yield and yield attributing traits.The crosses viz. OIJ-268 x S-19 (32.52; 27.1g/plant),OIJ248 x OMU-19 (19.52; 21.5g/plant),OMU-37 x OMU-27 (19.43; 18.7g/plant), OIJ-05 x JRO-204 (16.61; 20.1g/ plant), and OIJ-165xOIN-255 (12.61; 20.9g/plant)were identified as best combinations for fibre yield based on SCA effects and per se performance. These crosses also revealed significant amount of heterosis (range; 16.6- 68.9%) for fibre yield.The present study was usefull in identifying best general and specific combiners for exploitation of heterosis in jute breeding. Tossa jute